Evaluation and comparison of the effect of 10% sodium ascorbate and propolis solution on the microtensile bond strength and resin tag penetration depth of composite after using 35% carbamide peroxide bleaching agent - An in vitro study - Archa Anil; Liza George; Prasanth Dhanapal; Priya Thomas; Sinju Paul (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to evaluate and compare the effect of 10% sodium ascorbate and propolis solution on the microtensile bond strength (MTBS) and resin tag penetration depth of composite after using 35% carbamide peroxide bleaching agent. Materials and Method: Sixty extracted human premolars were divided into five groups with 12 samples in each. Group I samples did not receive bleaching treatment and served as control. Group II samples were bonded with composite 2 weeks later, while those in Group III were bonded immediately after bleaching. The samples in Group IV and Group V were treated with antioxidants 10% SA and propolis solution at the rate of 1ml/min for 10 min, respectively, before composite bonding. The samples were then sectioned mesiodistally into two halves. One half was subjected to MTBS testing using a Universal Testing Machine. The other half was decalcified, sectioned, stained, and viewed under an optical light microscope to assess the resin tag penetration. The results obtained were statistically analyzed using a one-way analysis of variance followed by Post hoc test. Results: Group III showed significantly lower MTBS and resin tag penetration depth of composite compared to all other groups. Group V (propolis group) showed statistical significance with all groups except Group IV (SA group). Conclusion: Treatment with antioxidant propolis solution immediately following the bleaching will help to reverse the compromised bond strength which is comparable with sodium ascorbate.